Common Errors in Composing An Academic Writing: A Descriptive Qualitative Study in Higher Education Setting - Wulandari Putri (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
This study was aimed at examining frequent errors found instudent academic writing, namely the abstract for proposal, as well as theirknowledge and problems they faced in composing an academic writing.The study was conducted in a descriptive qualitative method framework,involving students in an academic writing class. The participants of thestudy were seven students in the writing class. The instruments used inthis study were student works, focus group discussion, and a quiz. Theresults showed that the frequent errors found in student works includedthe use and selection of connectors, mechanical errors, redundancy,incorrect complex sentence structures, sentence structures (subject andpredicate agreement), and incomplete and/or inacurrate content. The mainproblems involved difficulties in arranging coherent writing, ordering theword correctly, choosing and selecting connectors, choosing formal words,and acknowledging the mistakes. Meanwhile, the data on studentknowledge showed that students had been aware of the structure of anabstract and all elements needed in an abstract. The findings imply thatinterventions for improving the student ability in evaluating their ownwork is vital, such as corrective feedback, the use of language tools, andextensive writing programs containing repetitive editing.